The Effectiveness of Online Learning Using Quizizz Education Game Media During the Covid-19 Pandemic in Applied Physics Courses - Safarati, Nanda; Rahma, Rahma (Indonesian Review of Physics (IRiP), 2020)
Online learning is learning that is applied by all educational institutions today. The use of appropriate media can support student effectiveness in education, especially in applied physics courses. This study aims to see online learning's effectiveness using quizizz educational media during the covid-19 pandemic in applied physics courses. This research uses a descriptive research method. The population in this study were students of the Almuslim University Physics Education Study Program. The sample selection used a purposive sampling method, namely students who were taking applied physics lectures. The data collection techniques used were tests (quizzes) and questionnaires. This study indicates that quizizz educational game media is one of the most effective online learning media used during the Covid-19 pandemic in applied physics courses.